ADPKD: Prototype of Cardiorenal Syndrome Type 4 - Virzì, Grazia Maria (SAGE-Hindawi Access to Research, 2010)
The cardiorenal syndrome type 4 (Chronic Renocardiac Syndrome) is characterized by a condition of primary chronic kidney disease (CKD) that leads to an impairment of the cardiac function, ventricular hypertrophy, diastolic dysfunction, and/or increased risk of adverse cardiovascular events. Clinically, it is very difficult to distinguish between CRS type 2 (Chronic Cardiorenal Syndrome) and CRS type 4 (Chronic Renocardiac Syndrome) because often it is not clear whether the primary cause of the syndrome depends on the heart or the kidney. Autosomal dominant polycystic kidney disease (ADPKD), a genetic disease that causes CKD, could be viewed as an ideal prototype of CRS type 4 because it is certain that the primary cause of cardiorenal syndrome is the kidney disease. In this paper, we will briefly review the epidemiology of ADPKD, conventional and novel biomarkers which may be useful in following the disease process, and prevention and treatment strategies.